2022
DOI: 10.1155/2022/1125877
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Removal of Hydroquinone and Resorcinol by Activated Carbon Based on Shea Residue (Vitellaria paradoxa): Thermodynamics, Adsorption Mechanism, Nonlinear Kinetics, and Isotherms

Abstract: The present work demonstrates the adsorption of hydroquinone (HQ) and resorcinol (R) by activated carbon based on shea residue (Vitellaria paradoxa). The adsorbent was prepared chemically by impregnation with sulfuric acid and coded by the acronym CAK-S. The central composite design (CCD) was used to optimize the main factors that influence the adsorption of HQ or R by activated carbon such as the initial concentration, the pH of the solution, the contact time, and the mass of the carbon on the expected respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 41 publications
(48 reference statements)
3
7
0
Order By: Relevance
“…This favours the formation of ACs of large specific surface areas and a marked increase in the porosity. These results are in agreement with those obtained by Amola et al [15].
Figure 2( a ) Pareto diagram of CRP and ( b ) Pareto diagram of CRB.
Figure 3Response surface of CRB ( a ) concentration and time with fixed temperature 400°C and ( b ) iodine number according to the temperature and time with a fixed concentration of 1 mol l −1 .
Figure 4Response surface of CRP ( a ) concentration and time with fixed temperature 400°C and ( b ) iodine number according to the temperature and time with a fixed concentration of 1 mol l −1 .
…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…This favours the formation of ACs of large specific surface areas and a marked increase in the porosity. These results are in agreement with those obtained by Amola et al [15].
Figure 2( a ) Pareto diagram of CRP and ( b ) Pareto diagram of CRB.
Figure 3Response surface of CRB ( a ) concentration and time with fixed temperature 400°C and ( b ) iodine number according to the temperature and time with a fixed concentration of 1 mol l −1 .
Figure 4Response surface of CRP ( a ) concentration and time with fixed temperature 400°C and ( b ) iodine number according to the temperature and time with a fixed concentration of 1 mol l −1 .
…”
Section: Resultssupporting
confidence: 94%
“…This favours the formation of ACs of large specific surface areas and a marked increase in the porosity. These results are in agreement with those obtained by Amola et al [15]. According to figures 2-4, it is also found that the concentration of the activating agents has a significant effect on the microporosity of said carbons; however, this factor is positive for the adsorption of iodine on CRP and negative on the CRB.…”
Section: Experimental Designsupporting
confidence: 92%
See 2 more Smart Citations
“…e use of biomass waste for the preparation of porous activated carbon has increased considerably in recent years. Some of the residual biomasses used for the manufacture of activated carbons are coffee waste [9], tucumã seeds [10], Ayous sawdust and Cucurbitaceae peelings [12], rice and coffee husks [13], olives stones and cotton cake [14], Vitellaria paradoxa [15], and rice hull and tamarind (T. indica) seeds [16].…”
Section: Introductionmentioning
confidence: 99%